The big brown pot - Mahy, Margaret; Rigby, Deborah Forss, Ian Scott, Janine (Autumn Publishing Chichester, 2013)
The Big Brown Pot: On the way in his little red car to share a big pot of stew with his friend, Mr. Winkle is unaware of the long procession forming behind him. A Parcel for Wilma W. Willis: A flipping, flopping parcel has many adventures before it arrives on the doorstep of Wilma the walrus. Book includes ideas for parents to help children understand the text and build reading skills